Efeitos da terapia de integração sensorial de Ayres nas atividades de vida diária e participação de crianças com transtorno de espectro do autismo - Izabela Lambertucci Cardoso (2023)
Introduction: More than 90% of people with autism spectrum disorder (ASD) have some sensory integration disorder. Sensory problems can lead to low participation in activities of daily living, emotional and behavioral problems, poor motor performance and learning. As a result, Ayres Sensory Integration Therapy has come to be considered an evidence-based practice for the treatment of autism, with the aim of reducing challenges related to sensory processing, increasing social participation and improving occupational performance. However, there is no consensus between research methods, generating an inconsistency in the scientific literature. Objective: To investigate the effects of Ayres Sensory Integration Therapy on activities of daily living and participation of Brazilian preschool children diagnosed with ASD. Methodology: Quasi-experimental study, with non-concurrent multiple baselines between subjects. Conducted with 9 children diagnosed with ASD, aged 3 to 6 years. Thirty sessions were held, twice a week, lasting 50 minutes, following a fidelity measure of Sensory Integration by Ayres. The instruments were the Sensory Profile 2, Autism Classification System: Social Communication (ACSF:SC), Pediatric Disability Assessment Inventory (PEDI), Canadian Occupational Performance Measure (COPM) and Goal Assessment Scale (GAS). The socioeconomic profile of the sample was obtained using the Brazilian Economic Classification Criteria (CCEB). Results: Significant improvements (p<0,05) were identified after the intervention in the exploration pattern and oral system (Sensory Profile 2), in social communication performance (ACSF:SC), in the functional skills of self-care and Mobility and caregiver assistance for self-care (PEDI) and in the functional objectives listed by the families (GAS). Final considerations: The results of this study suggest that the use of ASI therapy can contribute to the improvement of participation and performance in activities of daily living of younger children with ASD, with different levels of support. Still, there is an indication for exploring future research on a combination of family-centered practices and SI principles.